The role of Sudoscan feet asymmetry in the diabetic foot. Issue 1 (February 2020) - Gatev, Tsvetan; Gateva, Antoaneta; Assyov, Yavor; Nacheva, Sylvia; Petrova, Julia; Poromanski, Ivan; Kamenov, Zdravko
Highlights: Sudoscan feet asymmetry was higher in subjects with diabetic foot. This parameter proved as a discriminative and predictive tool for diabetic foot. From a ROC analysis was set a feet asymmetry cut-off of 9.5% for diabetic foot. Sudoscan hand asymmetry is also higher in participants with diabetic foot. Changes in Sudoscan symmetry appeared earlier than those in extremities. Abstract: The aim of this study was to investigate the role of Sudoscan asymmetry parameters in the diabetic foot. Patients and methods: In this study we included 165 participants: 84 type 2 diabetes patients divided into three HbA1c matched groups – group 1: newly diagnosed diabetics (n = 31), group 2: people with longer diabetes duration and established neuropathy (n = 33), group 3: patients with diabetic foot ulcer (n = 20), and a control group of 81 people with prediabetes. All subjects underwent peripheral sudomotor evaluation using Sudoscan device (Impeto Medical, Paris). Results: Patients with diabetic foot had significantly higher Sudoscan feet asymmetry (19.6%) compared to those with only diabetic neuropathy (7.9%), compared to the group with newly diagnosed diabetes (7.44%), and compared to controls (2.5%). This test has shown a good discriminative value (with a threshold of 9.5%) for diabetic foot with area under the ROC curve of 0.955 (p = 0.001). Additionally, in a regression model feet asymmetry proved its predictive value for participants with diabetic foot. Conclusion: In this study Sudoscan feet asymmetry proved to be a novel discriminator and predictor for diabetic foot patients. It might be considered as a marker for early damage in the neuropathy evaluation protocol.